A survey on comparison of electric motor types and drives used for electric vehicles - Yıldırım, Merve; Polat, Mehmet; Kürüm, Hasan (My University, 2014)
In this study, Switched Reluctance Motor (SRM), Induction Motor (IM), Brushless DC Motor, and Permanent Magnet Motor (PM), and their drives have been compared with the efficiency, cost, weight, cooling, maximum speed, reliability, fault tolerance, power ratings, and vehicle acceleration time. Hence, a comprehensive literature research on motor types and their drives used in EV has been made. According to these researches, some conclusions have been obtained. It has been seen that PM BLDC motors and their drives are the most efficient and have high power density, brushless DC motors and their drives have low cost, IM is appropriate for controllability and cost, the weight of SRM is low, its reliability is high, it operates fault-tolerance and according to the acceleration time, its performance is better than IM and BLDC. Hence, SRM is the most appropriate motor for EV.
Bildiri - Yayımlanmamış
Bildiri - Kongre ve Sempozyum
Keywords: Electrical vehicle motors and their drives; Comparison